Perlindungan Hukum Terhadap Anak Yang Menjadi Korban Bullying - Amisha Auralia Putri; Alina Nisviani; Wanda Hafisya; Suryadi Suryadi (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This research describes cases of bullying among students, especially in Tanjungpinang City, which are of serious concern because of their damaging impact both emotionally and physically on the victims. This phenomenon continues and forms a cycle that is difficult to break, starting from social pressure to aggressive actions carried out both verbally, physically and relationally. Of course, this cannot be separated from the role of education and educators. This research aims to examine the prevalence, forms and impacts of bullying in the school environment, as well as exploring available legal protection measures. The research used is a normative legal approach by referring to statutory regulations and a conceptual approach in the analysis of legal materials. The results of the analysis show that bullying, whether verbal, physical, or relational, has a significant impact on victims, such as mental health disorders, decreased academic achievement, and sleep disorders. On the other hand, bullies are also vulnerable to psychological problems and serious legal risks.